Persepsi Masyarakat Terhadap Wisata Mangrove di Desa Pante Deere, Kecamatan Kabola, Kabupaten Alor - Paulus Edison Plaimo; Imanuel Lamma Wabang (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
This study aims to determine public perceptions regarding the management of mangrove tourism areas in Pante Deere Village, Kabola District, Alor Regency, East Nusa Tenggara. The research method used is the Likert scale. The results of the research regarding the benefits or benefits obtained related to the existence of mangrove forest areas, 81% of respondents stated strongly agree; 4% agree; 4% Neutral; 5% Disagree and 6% strongly Disagree; Furthermore, mangrove tourism has an effect on people's income or economy, 74% of respondents and 10% stated strongly agree and agree, while 10% are neutral, while 6% and 5% disagree and strongly disagree; then related to the need for improvement or improvement of the quality of mangrove tourism assets, 86% of respondents stated strongly agree; 9% agree; 5% Neutral; Meanwhile, to give sanctions to anyone who takes/cut down Mangrove trees in the Mangrove Forest Tourism area, it turns out that the majority or 100% of respondents stated that they strongly agreed.